Evaluasi Keragaman Genetik Plasma Nutfah Jewawut (Setaria Italica (L.) P. Beauv.) Indonesia Menggunakan Marka Simple Sequence Repeats (SSRs) - Ramlah, Ramlah; Pabendon , Marcia Bunga; Daryono, Budi Setiadi (Biogenesis: Jurnal Ilmiah Biologi, 2026)
Foxtail millet (Setaria italica (L.) P. Beauv.) is cultivated in arid and semi-arid regions of Indonesia, yet genetic information on Indonesian germplasm remains limited. This study assessed the genetic diversity and population structure of 21 foxtail millet accessions collected from five Indonesian provinces using 30 polymorphic SSR markers distributed across nine chromosomes. DNA was extracted from 12-14-day-old seedlings and amplified by PCR with annealing temperatures ranging from 50 to 57°C. The polymorphic information content (PIC) was calculated using PowerMarker v3.25, while cluster analysis, genetic distance matrices, and Principal Coordinate Analysis (PCA) were performed using NTSYS-pc 2.1. Cophenetic correlation analysis was conducted using WinBoot software. Results revealed moderate to high genetic diversity with PIC values ranging from 0.09 (b190) to 0.78 (p16, b247, b223), averaging 0.54. A total of 100 alleles were detected with 2-6 alleles per locus. UPGMA-based cluster analysis grouped the germplasm into two main clusters at a similarity coefficient of 0.28, with Cluster I containing 11 accessions and Cluster II containing 10 accessions. Genetic distance values ranged from 0.11 (Minna' and Lasse') to 0.87 (ICE-276-12B-1 and Balla Pulut/Wete), indicating substantial genetic variation. PCA analysis confirmed the clustering pattern, with a strong cophenetic correlation (r = 0.81; good fit).